2018
DOI: 10.3847/1538-4357/aaec79
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Double: ASASSN-18bt Exhibits a Two-component Rise in the Early-time K2 Light Curve

Abstract: On 2018 February 4.41, the All-Sky Automated Survey for SuperNovae (ASAS-SN) discovered ASASSN-18bt in the K2 Campaign 16 field. With a redshift of z=0.01098 and a peak apparent magnitude of B max =14.31, ASASSN-18bt is the nearest and brightest SNe Ia yet observed by the Kepler spacecraft. Here we present the discovery of ASASSN-18bt, the K2 light curve, and prediscovery data from ASAS-SN and the Asteroid Terrestrial-impact Last Alert System. The K2 early-time light curve has an unprecedented 30-minute ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 87 publications
(119 reference statements)
7
80
0
Order By: Relevance
“…An early linear phase in the light curve of SN 2013dy was observed by Zheng et al (2013), and observations of SN 2014J show evidence for additional early-time structure (Zheng et al 2014;Goobar et al 2015;Siverd et al 2015). Contreras et al (2018) found that the light curve of SN 2012fr had an initial roughly linear phase that lasted for ∼ 2.5 days, and K2 observations of ASASSN-18bt showed a similar ∼ 4 day linear phase (Brown et al 2018;Shappee et al 2019;Li et al 2019;Dimitriadis et al 2019a). Additionally, Marion et al (2016) found potential indications of interaction with a non-degenerate binary companion in SN 2012cg, although this interpretation is challenged by Shappee et al (2018).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…An early linear phase in the light curve of SN 2013dy was observed by Zheng et al (2013), and observations of SN 2014J show evidence for additional early-time structure (Zheng et al 2014;Goobar et al 2015;Siverd et al 2015). Contreras et al (2018) found that the light curve of SN 2012fr had an initial roughly linear phase that lasted for ∼ 2.5 days, and K2 observations of ASASSN-18bt showed a similar ∼ 4 day linear phase (Brown et al 2018;Shappee et al 2019;Li et al 2019;Dimitriadis et al 2019a). Additionally, Marion et al (2016) found potential indications of interaction with a non-degenerate binary companion in SN 2012cg, although this interpretation is challenged by Shappee et al (2018).…”
Section: Introductionmentioning
confidence: 84%
“…However, TESS covers a much larger area of the sky, and will be able to observe significantly more SNe over the duration of its two year mission. So far, six SNe have been published from the Kepler and K2 missions (Olling et al 2015;Garnavich et al 2016;Shappee et al 2019), whereas TESS will obtain obtain relatively high precision light curves for ∼ 130 SNe (∼100 SNe Ia, and ∼ 30 SNe II; Fausnaugh et al 2019). These observations will provide an unparalleled sample of early-time SN light curves.…”
Section: Discussionmentioning
confidence: 99%
“…2014) but has stringent limits on stripped material emission (this work, Table B5). Similarly, ASASSN-18bt showed a two-component rising light curve (Shappee et al 2019;Dimitriadis et al 2019b), a potential signature for SN ejecta impacting a nearby companion (Kasen 2010). However, nebular spectra rule out any stripped material emission with strict upper limits (Tucker et al 2018;Dimitriadis et al 2019a, this work).…”
Section: The Lack Of a Consistent Theory For Sne Ia Progenitorsmentioning
confidence: 95%
“…Recently, similar analyses have been performed for an increasing number of SNe Ia with sufficiently early light curve data available (e.g., SN 2009ig;, KSN 2011aOlling et al 2015, KSN 2011bOlling et al 2015Silverman et al 2012b;Marion et al 2016;Shappee et al 2018Contreras et al 2018Yamanaka et al 2014Zheng et al 2013Holmbo et al 2018Goobar et al 2015, ASASSN-14lp;Shappee et al 2016Im et al 2015Dimitriadis et al 2019;Shappee et al 2019, Bianco et al 2011. For most, if not all, of normal SNe Ia, these analyses ruled out a giant companion for these SNe Ia, as is similar to SN 2019ein studied here.…”
Section: Prep)mentioning
confidence: 99%
“…As an example, the observations of SN 2011fe within one day since the explosion provided a strong constraint (≤ 0.1 − 0.25R ⊙ ; Nugent et al 2011, Goobar et al 2015. In the last decade, there are an increasing number of NV SNe for which similar constraints have been placed (e.g., Bianco et al 2011;Silverman et al 2012b;Zheng et al 2013;Yamanaka et al 2014;Goobar et al 2015;Im et al 2015;Olling et al 2015;Marion et al 2016;Shappee et al 2016;Hosseinzadeh et al 2017;Contreras et al 2018;Holmbo et al 2018;Miller et al 2018;Shappee et al 2018;Dimitriadis et al 2019;Shappee et al 2019). At the same time, diverse nature of the earliest light curve properties has also been noticed.…”
Section: Introductionmentioning
confidence: 97%